Numerical Simulation of Heat Transfer in Rectangular Microchannel (Advances in Applied Mathematics and Mechanics, 2018)
Numerical simulation of heat transfer in a high aspect ratio rectangularmicrochannel with heat sinks has been conducted, similar to an experimental study.Three channel heights measuring 0.3 mm, 0.6 mm and 1 mm are considered and theReynolds number varies from 300 to 2360, based on the hydraulic diameter. Simulationstarts with the validation study on the Nusselt number and the Poiseuillenumber variations along the channel streamwise direction. It is found that the predictedNusselt number has shown very good agreement with the theoretical estimation,but some discrepancies are noted in the Poiseuille number comparison. Thisobservation however is in consistent with conclusions made by other researchersfor the same flow problem. Simulation continues on the evaluation of heat transfercharacteristics, namely the friction factor and the thermal resistance. It is foundthat noticeable scaling effect happens at small channel height of 0.3 mm and thepredicted friction factor agrees fairly well with an experimental based correlation.Present simulation further reveals that the thermal resistance is low at small channelheight, indicating that the heat transfer performance can be enhanced with thedecrease of the channel height.